"Making it Real" Time. (June 2013) - Vrana, Kent E.
It has been 30 years since the first description of the polymerase chain reaction (PCR)—corresponding, coincidentally, with the year of the first issue of BioTechniques. Ensuing decades have seen remarkable advances in this revolutionary technique. Central to these approaches was the creation of paradigms for monitoring the progress of PCR amplification in real time. One of these seminal reports appeared in BioTechniques in 1997, establishing the double-strand-specific dye SYBR Green as a workhorse tool for continuous monitoring of DNA amplification.